(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Hematomas, particularly those involving the subdural cavity, are a significant cause of morbidity and mortality, often requiring prompt diagnosis and management. Various factors influence the severity and progression of hematomas, among which diabetes mellitus has emerged as a potential exacerbating condition Objective: To evaluate the impact of diabetes on the severity of subdural hematomas (SDH) using CT imaging by correlating glycemic control with hematoma volume and midline shift in diabetic and non-diabetic patients. Methodology: A descriptive cross-sectional study was conducted at Services Hospital, Lahore, over a time of three months. A total of 110 participants, including 55 diabetic and 55 non-diabetic individuals aged 18 to 60 years. The sample size was determined using a 90% confidence level and 80% power, with estimated proportions of 0.4 in the diabetic group and 0.14 in the non-diabetic group. Patients with other metabolic disorders and pregnant females were excluded. Results: A higher frequency of severe hematoma volume was observed in diabetic patients, while non-diabetic patients predominantly presented with mild hematomas, indicating a potential link between diabetes and hematoma severity. Similarly, diabetic patients exhibited a greater number of moderate midline shifts and Glasgow coma scale GCS in contrast to non-diabetic patients, suggesting that diabetes may contribute to increased intracranial pressure. Conclusion: DM has significantly impact on the severity of subdural hematomas. In diabetic patients it show greater midline shifts, hematoma volume and poor glycemic control than non-diabetic patients.